P396Impact of re-definition of paroxysmal and persistent atrial fibrillation in the 2012 and 2016 ESC atrial fibrillation guidelines on outcomes after cryoballoon pulmonary vein. (18th June 2020) - Aktolga, D; Weinmann, K; Rattka, M; Bothner, C; Stephan, T; Pott, A; Rottbauer, W; Dahme, T
Abstract: Introduction – In the 2016 European Society of Cardiology (ESC) guidelines for the management of atrial fibrillation (AF) the definition of AF type has been modified compared to the 2010 guidelines and its 2012 focused update. Purpose – Our aim was to compare the difference of single procedure outcomes using the definitions before and after 2016 on a cohort of patients with AF undergoing cryoballoon pulmonary vein isolation (PVI). Methods – Consecutive PVI patients with paroxysmal or persistent AF were retrospectively reclassified applying the 2010, 2012 and 2016 ESC definitions on AF type. Results – 628 patients were included in the analysis. Applying the 2010 ESC AF guidelines definition, 68% (425/628) of patients were categorized as paroxysmal and 32% (203/628) as persistent AF. According to the 2012 focused update 77% (485/628) are labeled paroxysmal and 23% (143/628) are persistent AF. Applying the 2016 ESC AF guidelines, the proportion of patients with paroxysmal AF increased to 87% (546/628) of patients and the patients with persistent AF decreased to 13% (82/628). Comparing the 2010 and 2016 ESC AF type definitions, 123 patients shift from the 2010 persistent group to the 2016 paroxysmal group. Age, left ventricular ejection fraction (LVEF), LA diameter and CHA2DS2-VASc Score differ significantly between paroxysmal and persistent AF patients according to the 2010, 2012, and 2016 AF type classification. Regarding outcomes, recurrence rates of paroxysmal and persistent AF patients differ significantly in Kaplan-Meier estimation applying the 2010 ESC guidelines definition (log-rank p < 0.001). Applying the 2012 focused update and the 2016 ESC AF guidelines recurrence rates do not differ significantly. Persistent AF has been shown repeatedly to be a predictor of arrhythmia recurrence in PVI studies. In a cox regression model applying the 2010 guidelines, persistent AF is the only independent predictor for AF recurrence in our cohort. However, when applying the 2016 guidelines persistent AF is no longer a predictor for AF recurrence. Conclusion – The revised definition of AF types in the 2016 ESC AF guidelines leads to a marked shift from persistent to paroxysmal AF. It appears that the old definition was a better separator to predict rhythm outcome after PVI.